Comparison of Antioxidative Effects of Insect Tea and Its Raw Tea (Kuding Tea) Polyphenols in Kunming Mice - Zhao, Xin (Molecules, 2018)
Kudingcha is a traditional Chinese tea, and insect tea is a special drink produced by the metabolism of insect larvae using the raw Kuding tea. Insect tea polyphenols (ITP) and its raw tea (Kuding tea) polyphenols (KTP) are high-purity polyphenols extracted by centrifuge precipitation. The present study was designed to compare the antioxidative effects of insect tea polyphenols (ITP) and its raw tea (Kuding tea) polyphenols (KTP) on d-galactose-induced oxidation in Kunming (KM) mice. KM mice were treated with ITP (200 mg/kg) and KTP (200 mg/kg) by gavage, and vitamin C (VC, 200 mg/kg) was also used as a positive control by gavage. After determination in serum, liver and spleen, ITP-treated mice showed higher superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and glutathione (GSH) activities and lower nitric oxide (NO), malonaldehyde (MDA) activities than VC-treated mice, KTP-treated mice and untreated oxidation mice (control group). By H&E section observation, the mice induced by d-galactose-induced oxidation showed more changes than normal mice, and oxidative damage appeared in liver and spleen tissues; ITP, VC and KTP improved oxidative damage of liver and spleen tissues, and the effects of ITP were better than VC and KTP. Using quantitative polymerase chain reaction (qPCR) and western blot experiments, it was observed that ITP could increase the mRNA and protein expression of neuronal nitric oxide synthase (nNOS), endothelial nitric oxide synthase (eNOS), manganese superoxide dismutase (Mn-SOD), cupro/zinc superoxide dismutase (Cu/Zn-SOD), catalase (CAT), heme oxygenase-1 (HO-1), nuclear factor erythroid 2 related factor 2 (Nrf2), gamma glutamylcysteine synthetase (γ-GCS), and NAD(P)H:quinone oxidoreductase 1 (NQO1) and reduce inducible nitric oxide synthase (iNOS) expression in liver and spleen tissues compared to the control group. These effects were stronger than for VC and KTP. Both ITP and KTP had good antioxidative effects, and after the transformation of insects, the effects of ITP were better than that of KTP and even better than VC. Thus, ITP can be used as an antioxidant and anti-ageing functional food.